Investigation of γ-(U,Zr) structural properties and its interfacial properties with liquid sodium using ab initio molecular dynamics - Aly, Ahmed; Beeler, Benjamin; Avramova, Maria (Journal of nuclear materials, 2022)
In this study, the elastic properties, structural parameters, sound velocity, and Debye temperature of γ−(U,Zr) were computed using ab initio molecular dynamics (AIMD) at temperatures between 1000 K and 1400 K and for Zr content between 0 at.% and 100 at.%. UZr is used as a metallic fuel for Sodium Fast Reactors (SFRs). The study of the mechanical and thermal behavior of these alloys leads to a better data-informed fuel design. The bulk modulus, shear modulus, Young’s modulus, and Poisson’s ratio were calculated from the elastic constants and their dependence on Zr content and temperature was investigated, comparing the results with previous computational work and the available experimental data in the literature. Interfacial properties between UZr (up to 32 at.% which typically exists in nuclear fuel) and liquid sodium are also of interest due to the presence of a sodium bond between the fuel and the cladding in metallic nuclear fuel. The interfacial energy between γ−(U,Zr) and liquid sodium, the surface tension of liquid sodium, and the work of adhesion were computed at different temperatures and Zr concentrations. It was demonstrated that γ−(U,Zr) is completely wetted by liquid sodium at all the investigated temperatures and Zr concentrations. This work provides the basis for the determination of interfacial resistances in SFRs and their implementation into heat transfer fuel performance simulations, which will be the subject of future work.